Application of Drill and Practice Method Assisted by Google Form to Improve Students' Accuracy in Mathematics Learning - Putri Jannati; Nina Rahayu; Faisal Arief Ramadhan (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
This study aims to find out how to apply the Drill and Practice Method using Google form media in learning mathematics in fraction material in class IV SDN Tmbang Langsa. The application of the drill and practice method is because at Timbang Langsa Elementary School the students still experience difficulties when participating in learning mathematics about fractions. The research method used is experimental, a type of quantitative research using interview and observation documentation. The subjects of this study were 15 students at SDN Timbang Langsa, and class IV teachers. The results of this study are the Google Form-based Drill and Practice Method applied at SDN Timbang Langsa because during the pandemic, students and teachers are connected via the Google form on their respective cellphones. Google Form-based Drill and Practice is implemented by giving questions and exercises repeatedly